2009
DOI: 10.1007/s12010-008-8498-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Low Molecular Weight Glycosaminoglycans from Marine Mollusc Amussium pleuronectus (Linne) using Chromatography

Abstract: The glycosaminoglycan (GAG) heparin is a polyanionic sulfated polysaccharide most recognized for its anticoagulant activity. In the present study, the GAGs were extracted from bivalve mollusc Amussium pleuronectus. The crude GAGs were fractionated by ion-exchange (DEAE-cellulose and Amberlite IRA-900 & 120) chromatography. The recovered active fractions (as determined by metachromatic assay) were confirmed by agarose gel electrophoresis and the active fractions were purified in Sephadex G-100 column. Fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Vidhyanandhini (2010) reported that the amount of crude GAGs was estimated as 9.85 gm/kg and after purification by using amberlite and barium acetate, the yield was found to be 33 and 148 mg/kg of K. opima. Saravanan and Shanmugam (2010) reported the amount of crude and purified GAG was estimated as 17.2 g/kg and 48 mg/kg of tissue in A. pleuronectus. The result of the present study clearly shows that the yield of heparin and heparin-like glycoasaminoglycans is higher and lower than those of previously reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vidhyanandhini (2010) reported that the amount of crude GAGs was estimated as 9.85 gm/kg and after purification by using amberlite and barium acetate, the yield was found to be 33 and 148 mg/kg of K. opima. Saravanan and Shanmugam (2010) reported the amount of crude and purified GAG was estimated as 17.2 g/kg and 48 mg/kg of tissue in A. pleuronectus. The result of the present study clearly shows that the yield of heparin and heparin-like glycoasaminoglycans is higher and lower than those of previously reports.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the anticoagulant GAGs from whole body tissue of D. faba crude and purified sample showed a major peaks at 3437. 15, 1639.49, 1251.8, 1197.79, 1128.36 and 1078.21 cm -1 which is said to be for the GAGs groups (Saravanan and Shanmugam, 2010 Besides the aforementioned, it could also have a very good anticoagulant activity as the anticoagulant compound from this species proves the possibility of its utilization as an additional potent source for the extraction of such anticoagulant compound since the anticoagulant activity of the presents isolated heparin and heparin like GAGs from D. faba was even more than that of many heparins obtained from commercial sources.…”
Section: Discussionmentioning
confidence: 99%
“…GAGs are long un-branched hetero-polysaccharides, widespread in nature, occurring in a great variety of organisms exhibiting various physiological and biological functions [29][30][31]. Figure 1 Decade-wise increase of marine compound discovery.…”
Section: Marine Glycobiologymentioning
confidence: 99%
“…79°46′ E), Tamil Nadu, India. The samples are defatted and processed to obtain crude glycosaminoglycan (GAG) [53]. The crude GAG is subjected to enzymatic depolymerization to obtain low molecular weight heparan sulfate (LMW-HS) and its purity was determined by PAGE and metachromatic activity.…”
Section: Marine Carbohydrate Based Drugs For Ndmentioning
confidence: 99%
“…These studies provide the key for novel drug treatments for a range of diseases, including cancer as well as various inflammatory diseases (Lever & Clive, 2002). Although commercial, pharmaceutical heparin preparations are strictly obtained from mammalian sources, marine mollusk have recently been identified as a potent alternative source for extraction of several heparin and LMWH-like polymers with high anticoagulant activity (Saravanan & Shanmugam, 2010;Periyasamy et al, 2013). Heparins [both unfractionated (UFH) and low molecular weight (LMWH) derivatives] remain as the agents of choice for pharmacologic thromboprophylaxis, treatment of thromboembolism during pregnancy, with pediatric patients and in myocardial infarction, cardiovascular surgery, coronary angioplasty and numerous other conditions (Eldor, 2002;Pineo et al, 2004;Greer, 2005;Baldwin et al, 2014;Molinari et al, 2014).…”
Section: Introductionmentioning
confidence: 99%